(3ebGdI GdEScfOQ GdEaQhOjSi aj Cf GdfThA hGdfeGA jchfGf aj GdUhQI dG aj Gdgjhdis - (3GdGScfOQ GdGaQhOjSjs
(3ChdgG (B:s
(3bGd GdEScfOQ (B: (3Ef CQSWhWGdjS PcQ ai cJGH Gdchf hGdaSGO GdfThA hGdfeG , jchfGf ai GdUhQI dG ai Gdgjhdi s
(3BNQgG (B:s
(3EJVM bhd GdajdSha (B: (3Ef GdfThA jchf ai GdUhQI dG ai GdYfUQ JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/11) s
Keywords: (3GdadSaI hGdefWbs